2012
DOI: 10.1007/s12254-012-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment of low grade gliomas

Abstract: Low grade gliomas affect predominantly young adults, and have a relatively favorable prognosis compared to grade III and grade IV gliomas. The challenge for an optimal management of these patients is to find the balance between an optimal survival and the preservation of neurological function including cognition. Because all medical treatments may induce side effects, in young and nearly asymptomatic patients the choices can be difficult. This review summarizes the current strategies: a watch-and-wait policy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…Patients with GIIG are usually young and often enjoy a good quality of life due to absent or only minor neurological deficits [1], which can be explained by neuroplasticity induced by these slow growing neoplasms [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with GIIG are usually young and often enjoy a good quality of life due to absent or only minor neurological deficits [1], which can be explained by neuroplasticity induced by these slow growing neoplasms [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This discovery is not unexpected, given the highly infiltrative nature of these tumours [77,96,97,191].…”
Section: The Benefits and Risks Of Surgerymentioning
confidence: 98%
“…The only drug on the list published by Kargiotis et al [109] this is not considered to interact with AEDs is temozolomide (TMZ), a less toxic and more-easily tolerated orally-administered drug that effectively crosses the blood-brain barrier [188] and is now commonly used for both high-grade [189] and low-grade [190,191] gliomas, as well as for brain metastases [192] and melanomas, often in combination with radiation therapy. There also is evidence that TMZ itself reduces the frequency of seizures, independent of AED dose.…”
Section: Aeds For Seizure Controlmentioning
confidence: 99%
“…A large randomized trial showed an increase in time to progression after early RT compared to RT at the time of progression [62] . Early RT (dose of 54 Gy in fractions of 1.8 Gy) improved median progression free survival from 3.4 to 5.3 years, indicating that the timing of RT is less relevant as long as it is given [63] . Reirradiation is frequently employed in recurrent glioma [64] .…”
Section: Radiation Therapymentioning
confidence: 99%